Ag nanoparticles immobilized sulfonated polyethersulfone/polyethersulfone electrospun nanofiber membrane for the removal of heavy metals - Talukder, Md Eman; Pervez, Md. Nahid; Jianming, Wang; Stylios, George K.; Hassan, Mohammad Mahbubul; Song, Hongchen; Naddeo, Vincenzo; Figoli, Alberto (Scientific reports, 2022)
In this work, Eucommia ulmoides leaf extract (EUOLstabilized silver nanoparticles (EUOL@AgNPs) incorporated sulfonated polyether sulfone (SPES)/polyethersulfone (PES) electrospun nanofiber membranes (SP ENMs) were prepared by electrospinning, and they were studied for the removal of lead (Pb(II)) and cadmium (Cd(II)) ions from aqueous solutions. The SP ENMs with various EUOL@AgNPs loadings were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscope, thermo-gravimetric analysis (TGA), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and contact angle (CA) measurements. The adsorption studies showed that the adsorption of Cd(II) and Pb(II) was rapid, achieved equilibrium within 40 min and 60 min, respectively and fitted with non-linear pseudo-second-order (PSO) kinetics model. For Cd(II) and Pb(II), the Freundlich model described the adsorption isotherm better than the Langmuir isotherm model. The maximum adsorption capacity for Cd(II) and Pb(II) was 625 and 370.37 mg g −1 respectively at neutral pH. Coexisting anions of fluoride, chloride, and nitrate had a negligible influence on Cd(II) removal than the Pb(II). On the other hand, the presence of silicate and phosphate considerably affected Cd(II) and Pb(II) adsorption. The recyclability, regeneration, and reusability of the fabricated EUOL@AgNPs-SP ENMs were studied and they retained their high adsorption capacity up to five cycles. The DFT measurements revealed that SP-5 ENMs exhibited the highest adsorption selectivity for Cd(II) and the measured binding energies for Cd(II), Pb(II), are 219.35 and 206.26 kcal mol −1 , respectively. The developed ENM adsorbent may find application for the removal of heavy metals from water.